Opening Up the Indexicality of the Image, Again - Christopher Ball; Meghanne Barker; Elizabeth Edwards; Tomáš Kolich; W. T. J. Mitchell; Daniel Morgan; Constantine V. Nakassis (Semiotic Review, 2020)
This virtual roundtable was conducted from May 10 to June 2, 2020 over e-mail, across several rounds of statements and responses. The participants were Christopher Ball (also Chris in the transcript below), Meghanne Barker, Elizabeth Edwards, Tomáš Kolich, W. J. T. Mitchell (also Tom in the transcript below), Daniel Morgan (also Dan in the transcript below), and Constantine V. Nakassis (also Costas in the transcript below), who also functioned as the moderator of the discussion. The editors of this special issue—Meghanne Barker and Constantine Nakassis—have lightly edited the text and integrated the comments in the order in which they were circulated to the group.